UJI COBA PERKEMBANGAN DAN HASIL PENELITIAN TANAMAN PAKCOY (BRASSICA RAPA CHINENSIS L) DENGAN PEMBERIAN PUPUK AB MIX PADA SISTEM HIDROPONIK - Mawarika, Auliya Intan (SIGNIFICANT : Journal Of Research And Multidisciplinary, 2023)
Nowadays, many people are reluctant to grow plants because in addition to taking a lot of time, limited land is also one of the problems of today's society, especially for farmers. However, various efforts can be made to overcome these problems, for example with hydroponic cultivation. Hydroponic systems can be applied to several types of plants, for example pakcoy mustard greens. The use of AB Mix fertilizer in hydroponic pakcoy plants has an influence on the growth of pakcoy plants. Providing appropriate nutrition to plants can provide optimal results. Therefore, I am interested in exploring the effect of AB Mix fertilizer on the growth of pakcoy plants with a hydroponic system. This study aims to determine the effect of pakcoy plants using AB mix fertilizer on hydroponic systems. This research is an experimental research and was conducted on September 16, 2021 at Perumnas Belitung, Prabumulih City, South Sumatra. The results of the experiment showed that the application of AB Mix fertilizer to pakcoy plants in the hydroponic system had an effect on plant height parameters (7 HST, 15 HST and 20 HST) and the number of leaves parameters (7 HST, 15 HST and 20 HST).